F Fragmentasi Standar Syariah dan Stabilitas Pasar Keuangan Islam: Analisis Peran Harmonisasi AAOIFI: Analisis Kritis Peran Harmonisasi AAOIFI dalam Mengurangi Fragmentasi Standar Syariah - Ikhsan Gasali; Iqbal Imari; Faranisa Saputri; Nabila Luthfiyani; Najwa Aulia Azzahra (FKIP Unswagati, 2026)
This study aims to analyze the impact of Sharia standard fragmentation on the stability of the Islamic financial market and to assess the role of AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) in mitigating the negative effects of cross-country interpretive differences. The research employs a qualitative descriptive method using a library research approach, drawing from journals, institutional reports (AAOIFI, IFSB, IsDB), and academic publications from 2020–2025. The findings indicate that Sharia standard fragmentation leads to regulatory inconsistencies, accounting disparities, and reduced investor confidence, which collectively increase market volatility and inefficiency. Conversely, comprehensive adoption of AAOIFI standards enhances transparency, strengthens governance in Islamic financial institutions, and supports macroeconomic stability through greater market integrity and regulatory alignment. The study concludes that harmonizing Sharia standards is essential for establishing a stable, efficient, and globally competitive Islamic financial system. Strong collaboration among regulators, financial institutions, and international standard-setting bodies is crucial to minimize fragmentation and reinforce the sustainability of Islamic finance worldwide. Keywords: Sharia Fragmentation, AAOIFI, Islamic Financial Stability, Harmonization